Innovations in maternal and child health: case studies from Uganda - Phyllis Awor; Maxencia Nabiryo; Lenore Manderson (BMC, 2020)
Abstract Background Nearly 300 children and 20 mothers die from preventable causes daily, in Uganda. Communities often identify and introduce pragmatic and lasting solutions to such challenging health problems. However, little is known of these solutions beyond their immediate surroundings. If local and pragmatic innovations were scaled-up, they could contribute to better health outcomes for larger populations. In 2017 an open call was made for local examples of community-based solutions that contribute to improving maternal and child health in Uganda. In this article, we describe three top innovative community-based solutions and their contributions to maternal health. Main text In this study, all innovations were implemented by non-government entities. Two case studies highlight the importance of bringing reproductive health and maternal delivery services closer to populations, through providing accessible shelters and maternity waiting homes in isolated areas. The third case study focuses on bringing obstetric imaging services to lower level rural health facilities, which usually do not provide this service, through task-shifting certain sonography services to midwives. Various health system and policy relevant lessons are highlighted. Conclusions The described case studies show how delays in access to health care by pregnant women in rural communities can be systematically removed, to improve pregnancy and delivery outcomes. Emphasis should be put on identification, capacity building and research to support the scale up of these community-based health solutions.